Impact of an intervention for recently released homeless offenders on self-reported re-arrest at 6 and 12 months. Issue 1 (2nd January 2017) - Nyamathi, Adeline; Salem, Benissa E.; Farabee, David; Hall, Elizabeth; Zhang, Sheldon; Faucette, Mark; Bond, Doug; Yadav, Kartik
ABSTRACT: A randomized controlled trial was conducted with 600 paroled men, homeless prior to incarceration, to assess varying levels of peer-coach and nurse-partnered interventions on re-arrest at 6 and 12 months. Findings revealed that positive predictors of re-arrest at 12 months included having received social support from drug users and non-drug users, as well as having used marijuana at least once a week prior to their most recent incarceration. In terms of protective factors, those who participated in a substance abuse program contract within a residential drug treatment program or spent 90 days or greater in a residential drug treatment program were less likely to have been re-arrested within 12 months.